"Defeaters" don't matter. (27th March 2018) - Ward, Zina B.; Machery, Edouard
Abstract: We argue that the exercise of agency is compatible with the presence of what Doris calls "defeaters." In order to undermine reflectivist theories of agency and support his valuational alternative, Doris must not simply show that defeaters exist but rather establish that some agentive behaviors do express a person's values without involving reflection.